Pengaruh Person Organization Fit terhadap Kinerja Pegawai Melalui Kepuasan Kerja sebagai Variabel Intervening pada Brida Provinsi Jambi - Jonathan Bastista Sinaga; Shofia Amin; Dian Mala Fithriani Aira (Trending: Jurnal Manajemen dan Ekonomi, 2025)
This study aims to analyze the effect of Person-Organization Fit on employee performance, with job satisfaction as an intervening variable at BRIDA Jambi Province. This study used a quantitative approach, with a population of 40 BRIDA employees, who also served as the research sample. Data were collected through a questionnaire that had been tested for validity and reliability. Data analysis was performed using Structural Equation Modeling (SEM) with the assistance of SmartPLS 4.0 (Partial Least Squares) software. The results showed that Person-Organization Fit had a positive and significant effect on employee performance and job satisfaction. Furthermore, job satisfaction also had a positive and significant effect on employee performance. Other findings indicated that Person-Organization Fit had a positive and significant effect on employee performance, through job satisfaction as an intervening variable. Thus, the fit between the individual and the organization has been proven to be a crucial factor in improving employee satisfaction and performance at BRIDA Jambi Province.